Macbeth; El Mercader de Venecia, Las alegres comadres de Windsor; Julio César; La tempestad. / William Shakespeare - Shakespeare, William (México : PORRÚA)
Obra literaria
Incluye: bibliografía, índice
Col. OGen
Keywords: 1. OBRAS GENERALES 2. LITERATURA